Incidence and risk factors for the diagnosis of lymphoma in dogs in UK primary‐care practice. (22nd July 2019) - Pittaway, C.; Schofield, I.; Dobson, J.; O'Neill, D. G.; Brodbelt, D. C.
Abstract : Objectives: To identify the incidence, risk factors and presenting signs of lymphoma in dogs presenting to primary‐care practice in the UK using analysis of data within the VetCompass™ programme. Materials and Methods: Case records from the VetCompass™ programme from primary‐care practices in the UK were searched for newly diagnosed lymphoma in dogs within a 1‐year period: 2013. Diagnosis was based on clinical records with or without laboratory confirmation. Signalment was evaluated as risk factors for lymphoma diagnosis using multivariable logistic regression. Results: There were 286 presumed newly diagnosed cases identified during 2013 from 455, 553 dogs (overall incidence risk 63 of 100, 000 dogs per year) of which 193 (67%) were laboratory confirmed (42 of 100, 000 dogs per year). Advanced age, dogs older than 12 years, dogs weighing more than 30 kg and some specific breeds were significantly associated with lymphoma diagnosis. Only 18 dogs (6%) of the population identified were referred to a specialist clinic. Clinical Significance: This study concurs with others that age, bodyweight and breed are significant risk factors for lymphoma. Results of this study highlight: (1) the low number of dogs with lymphoma that are referred to specialists in the UK and (2) that few dogs undergo immunophenotyping (which can carry prognostic importance), emphasising the importance of epidemiological programmes that evaluate diseases presented to primary‐care veterinarians.